Conductive copper paste, electrode and method for preparing conductive copper paste
By using phosphorus-containing elemental compounds as antioxidants in the conductive copper paste, combining resin and curing agent, a low-temperature cured conductive copper paste is solved, and excellent conductivity and resistance are achieved Oxidation, suitable for solar cells and other fields.
Patent Information
- Application Number
- CN202210680478.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-16
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-06-16
AI Technical Summary
The existing conductive copper slurry has oxidation problems, which leads to a reduction in conductivity, and the process is complex, which increases costs and is difficult to apply in industrial production.
Using phosphorus-containing compounds as antioxidants, adsorbs the surface of copper powder through coordination bonds to form a dense molecular film layer, and combining resin and curing agent to form a low-temperature cured conductive copper paste, including copper powder, resin, curing agent, accelerator, Antioxidants, solvents and conductive reinforcement fillers.
It realizes excellent conductivity and oxidation resistance of conductive copper paste, reduces the complexity and cost of production processes, is suitable for industrial production, and has a low curing temperature, and is suitable for solar cells and other fields.
Smart Images

Figure BDA0003698184420000131 
Figure BDA0003698184420000141 
Figure BDA0003698184420000151
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solar cells, and in particular to a conductive copper paste, an electrode, and a method for preparing the conductive copper paste. Background Art
[0002] In recent years, conductive metal pastes have been increasingly widely used in the fields of semiconductors, electronics, energy, and automobiles. At present, the mainstream market mainly uses silver powder as a conductive filler to prepare conductive pastes. Silver paste has excellent conductivity and oxidation resistance. However, the high price of silver has greatly hindered the widespread application and development of silver paste. In addition, silver migration is also one of the factors that affect the application of silver paste.
[0003] The conductivity of copper is second only to silver. However, compared with silver powder, copper powder is more easily oxidized, so the oxidizability of copper has become a bottleneck in the development of copper paste. In recent years, many documents and patent technologies on conductive copper paste have been made public. A commonly used anti-oxidation method is to coat or electroplate a layer of anti-oxidation metal shell on the surface of copper powder, such as silver-coated copper powder. However, due to the limitations of existing processes, the coating layer cannot completely cover the surface of copper powder, and there are often cracks and exposed defects, which eventually lead to oxidation of the copper core. At the same time, the use of silver also increases the cost of conductive copper paste; another method is to chemically modify the surface of copper particles, such as by treating with organic corrosion inhibitors such as benzotriazole, but its anti-oxidation and conductivity still need to be improved. In addition, the previous technology also has the problem of high curing temperature of conductive paste. The high curing temperature easily destroys the anti-oxidation layer on the surface of copper powder, thereby increasing the resistance of conductive copper paste. Summary of the invention
[0004] In view of the above problems, the present application proposes a conductive copper paste with simple process, low cost, good oxidation resistance and conductivity.
[0005] The technical solution of this application is as follows:
[0006] The present application provides a conductive copper paste, including copper powder, resin and antioxidant;
[0007] The antioxidant is a compound containing phosphorus.
[0008] Furthermore, the conductive copper paste also includes a curing agent, a accelerator, a solvent, an auxiliary agent and a conductive reinforcing filler.
[0009] Furthermore, based on the total weight of the conductive copper paste as 100%, the mass fraction of the copper powder is 78-90%, preferably 83-88%, or the mass fraction of the antioxidant is 0.5-1.5%, preferably 0.5-1.2%.
[0010] Furthermore, based on the total weight of the conductive copper paste as 100%, the mass fraction of the resin is 3 to 6.5%, preferably 3 to 5.5%, or
[0011] The mass fraction of the curing agent is 3 to 5.5%, preferably 3 to 5%, or
[0012] The mass fraction of the accelerator is 0.2-1%, preferably 0.2-0.6%, or
[0013] The mass fraction of the solvent is 1 to 5%, preferably 2 to 5%, or
[0014] The mass fraction of the auxiliary agent is 0.3-0.7%, preferably 0.3-0.6%, or
[0015] The mass fraction of the conductive reinforcing filler is 0.5-2%, preferably 0.5-1.5%.
[0016] Furthermore, the compound containing phosphorus is an inorganic phosphorus-containing compound or an organic phosphorus-containing compound, preferably an organic phosphorus-containing compound.
[0017] Furthermore, the inorganic phosphorus-containing compound is selected from one or more of phosphoric acid and its salts, pyrophosphate and its salts, phosphorous acid and its salts, metaphosphoric acid and its salts, hypophosphorous acid and its salts, preferably phosphate, pyrophosphate, phosphite, metaphosphate, hypophosphite.
[0018] Furthermore, the organic phosphorus-containing compound is selected from monobasic phosphate, monobasic hypophosphite, polybasic phosphate or polybasic phosphite, preferably monobasic phosphate.
[0019] Furthermore, the copper powder is selected from spherical, flaky or dendritic powders with a D50 of 100 nm to 10 μm.
[0020] Furthermore, the resin is selected from one or more of epoxy resin, polyurethane-modified epoxy resin, acrylic-modified epoxy resin, polyamide resin, saturated polyester resin, polyurethane resin, acrylic resin and silicone resin.
[0021] Furthermore, the curing agent is selected from one or more of polyamine, anhydride, polyamide, polyol and blocked isocyanate.
[0022] Furthermore, the accelerator is selected from one or more of tertiary amines, quaternary ammonium salts, imidazoles, pyridines, organic tins and boron trifluoride complexes.
[0023] Furthermore, the solvent is selected from one or more of a hydroxyl group-containing compound having 2 to 16 carbon atoms, an ether group-containing compound having 2 to 18 carbon atoms, a carbonyl group-containing compound having 3 to 12 carbon atoms, and an ester group-containing compound having 2 to 16 carbon atoms.
[0024] Furthermore, the auxiliary agent is selected from one or more of a dispersant, a coupling agent, an anti-settling agent and an acid-base regulator.
[0025] Furthermore, the conductive reinforcing filler is selected from one or more of silver powder, aluminum powder, nickel powder, tin powder, indium powder, carbon black, graphene and carbon nanotubes.
[0026] The present application provides a method for preparing a conductive copper paste, comprising the following steps:
[0027] Remove oxides and organic impurities from the surface of copper powder;
[0028] Preparation of resin carrier: adding resin and antioxidant into solvent, heating and dissolving to obtain resin carrier;
[0029] Slurry mixing: mixing and uniformly dispersing the copper powder from which oxides and organic impurities have been removed, conductive reinforcing filler, curing agent, accelerator, auxiliary agent and resin carrier to obtain the conductive copper slurry;
[0030] The antioxidant is a compound containing phosphorus.
[0031] Furthermore, an acid ethanol solution is used to clean oxides and organic impurities on the surface of the copper powder.
[0032] Furthermore, the mass volume ratio of the copper powder to the ethanol solution of the acid is 1 g: (1-2) ml;
[0033] In the acid ethanol solution, the mass fraction of the acid is 1-5%.
[0034] The acid is one of dilute hydrochloric acid, formic acid, oleic acid or phosphoric acid.
[0035] Furthermore, the conductive copper paste prepared by the method is the conductive copper paste according to any one of claims 1 to 14.
[0036] The present application provides an electrode, which is formed by coating the above-mentioned conductive copper paste on a substrate by screen printing.
[0037] The conductive copper paste provided by the present application has a pair of unbonded lone pairs of electrons in phosphorus atoms, which are easy to coordinate with metal atoms. When the copper powder is treated with phosphorus-containing compounds, the phosphorus-containing compounds are adsorbed on the surface of the copper powder in the form of coordination bonds to form a dense phosphorus-containing compound molecular film layer, thereby blocking the oxidation and corrosion of the copper powder by substances such as water and oxygen. In addition, the phosphorus-containing compounds are less volatile, have no odor, and cause less harm to operators. DETAILED DESCRIPTION
[0038] The following is a description of the exemplary embodiments of the present application, including various details of the embodiments of the present application to facilitate understanding, which should be considered as merely exemplary. Therefore, it should be recognized by those of ordinary skill in the art that various changes and modifications can be made to the embodiments described herein without departing from the scope and spirit of the present application. Similarly, for clarity and conciseness, the description of well-known functions and structures is omitted in the following description.
[0039] The Chinese patent application with application number 202111130893.8 describes a method of adding a compound antioxidant additive containing organic copper salts, thiols / nitrogen azoles, and amine compounds to a conductive copper slurry, thereby achieving the effect of improving the antioxidant properties of copper powder. However, since thiols / thiophenols have an unpleasant odor and have adverse effects on the physical and mental health of operators, they are restricted in industrial production. On the other hand, the patent requires the combination of three compounds that have an antioxidant effect on copper, and the copper powder needs to be pretreated with a solution of a compound antioxidant additive, which obviously increases the complexity of the production process.
[0040] Therefore, in order to solve the above problems without affecting the conductivity and oxidation resistance of the copper paste, the present application adopts compounds containing phosphorus to prepare conductive copper paste. Experimental verification has proved that the conductive copper paste with the addition of phosphorus-containing compounds has better conductivity and oxidation resistance, and the production process is simple, without the need to add additional steps, and is suitable for application in industrial production.
[0041] The conductive copper paste of the present application includes copper powder, resin, curing agent, accelerator, antioxidant, solvent, auxiliary agent and conductive reinforcing filler;
[0042] The antioxidant is a compound containing phosphorus.
[0043] Specifically, since the phosphorus atom in the antioxidant contains a pair of unbonded lone electrons, it is easy to coordinate with metal atoms. When the copper powder is treated with phosphorus-containing compounds, the phosphorus-containing compounds are adsorbed on the surface of the copper powder through coordination bonds to form a dense phosphorus-containing compound molecular film layer, thereby blocking the oxidation and corrosion of the copper powder by substances such as water and oxygen. In addition, phosphorus-containing compounds are less volatile, have no odor, and cause less harm to operators.
[0044] In the present application, the conductive copper paste is composed of copper powder, resin, curing agent, accelerator, antioxidant, solvent, auxiliary agent and conductive reinforcing filler; the antioxidant is a compound containing phosphorus element.
[0045] In the present application, the role of copper powder is to conduct electricity, and the copper particles contact each other to form a charge transfer path. The above-mentioned antioxidant is adsorbed on the surface of the copper powder in the form of coordination bonds, and a dense phosphorus-containing compound molecular film layer is formed on the surface of the copper powder, which provides long-term and stable antioxidant properties for the conductive copper slurry. The role of the resin is to form a skeleton. After curing, the resin molecules are connected to each other, thereby forming a close contact between the copper powders and between the copper powders and the substrate. The role of the curing agent is to connect the resin to form a thermosetting network structure. The role of the conductive reinforcing filler is to fill the gaps between the copper powders, enhance the contact between the copper powders and between the copper powders and the substrate (transparent conductive film), and increase the conductivity of the copper slurry. The role of the solvent is to disperse the above-mentioned other components in the solvent to form a slurry with a certain viscosity. The auxiliary agent is selected from at least one of a dispersant, a coupling agent, an anti-settling agent and an acid-base regulator, wherein the dispersant reduces the surface tension of the slurry so that the solid-liquid two phases form a uniform mixture; the coupling agent enhances the bonding force between the solidified slurry and the substrate (such as silicon wafer), thereby reducing the contact resistance; the anti-settling agent forms an electrostatic repulsion between the powders, thereby slowing down the sedimentation of the powders in the slurry; the acid-base regulator adjusts the pH value of the slurry to avoid the pH value of the slurry being too high or too low to affect its curing performance. The accelerator catalyzes the curing reaction, reduces the curing temperature and reduces the curing time.
[0046] In the present application, based on the total weight of the conductive copper paste as 100%, the mass fraction of the copper powder is 78-90%, the mass fraction of the resin is 3-6.5%, the mass fraction of the curing agent is 3-5.5%, the mass fraction of the accelerator is 0.2-1%, the mass fraction of the antioxidant is 0.5-1.5%, the mass fraction of the solvent is 1-5%, the mass fraction of the auxiliary agent is 0.3-0.7%, and the mass fraction of the conductive reinforcing filler is 0.5-2%.
[0047] Furthermore, based on the total weight of the conductive copper paste as 100%, the mass fraction of the copper powder is 83-88%, the mass fraction of the resin is 3-5.5%, the mass fraction of the curing agent is 3-5%, the mass fraction of the accelerator is 0.2-0.6%, the mass fraction of the antioxidant is 0.5-1.2%, the mass fraction of the solvent is 2-5%, the mass fraction of the auxiliary agent is 0.3-0.6%, and the mass fraction of the conductive reinforcing filler is 0.5-1.5%.
[0048] In the present application, based on the total weight of the conductive copper paste as 100%, the mass fraction of the copper powder can be 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89% or 90%.
[0049] Taking the total weight of the conductive copper paste as 100%, the mass fraction of the resin may be 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6%, 6.1%, 6.2%, 6.3%, 6.4% or 6.5%.
[0050] Based on the total weight of the conductive copper paste as 100%, the mass fraction of the curing agent may be 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4% or 5.5%.
[0051] Based on the total weight of the conductive copper paste as 100%, the mass fraction of the accelerator may be 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%.
[0052] Based on the total weight of the conductive copper paste as 100%, the mass fraction of the antioxidant may be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4% or 1.5%.
[0053] Taking the total weight of the conductive copper paste as 100%, the mass fraction of the solvent may be 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9% or 5%.
[0054] Based on the total weight of the conductive copper paste being 100%, the mass fraction of the auxiliary agent may be 0.3%, 0.4%, 0.5%, 0.6% or 0.7%.
[0055] Based on the total weight of the conductive copper paste as 100%, the mass fraction of the conductive reinforcing filler may be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%.
[0056] In the present application, the compound containing phosphorus element is an inorganic phosphorus-containing compound or an organic phosphorus-containing compound, preferably an organic phosphorus-containing compound.
[0057] Specifically, the inorganic phosphorus-containing compound is selected from one or more of phosphoric acid and its salts, pyrophosphate and its salts, phosphorous acid and its salts, metaphosphoric acid and its salts, hypophosphorous acid and its salts, preferably phosphate, pyrophosphate, phosphite, metaphosphate, hypophosphorous acid. For example, it can be phosphoric acid, copper pyrophosphate, including but not limited to these.
[0058] Specifically, the organic phosphorus-containing compound is selected from phosphoric acid monoester, hypophosphite monoester, phosphoric acid polyester or phosphite polyester, preferably phosphoric acid monoester.
[0059] Specifically, for example, the monobasic phosphate can be octadecyl monophosphate, n-dodecyl phosphate, ethanolamine phosphate, butyl phosphate, monopentyl phosphate, hexyl phosphate, heptyl dihydrogen phosphate, n-heptyl phosphate, n-octyl phosphate, n-tetradecyl phosphate, etc., including but not limited to these.
[0060] Furthermore, the monobasic phosphate is preferably a C4-C18 linear alkyl phosphate monoester. The C4-C18 linear alkyl phosphate monoester is produced by phosphoric acid and a C4-C18 linear alkanol.
[0061] The linear alkyl phosphate monoester has a long-chain alkyl structure, and the alkyl group can form a good hydrophobic layer, effectively blocking water and oxygen intrusion, so the linear alkyl phosphate monoester generally has a better antioxidant effect. The linear alkyl phosphate monoester has better antioxidant properties than the phosphate containing heterochain, because when the phosphorus atom is adsorbed on the surface of the copper powder, the chain stretches outward, and the linear chain is easily arranged into an orderly, consistent molecular layer. However, due to the influence of steric hindrance, the heterochain is relatively disorderly arranged, so its molecular layer has more defects, and accordingly, the antioxidant effect is slightly poor.
[0062] The monophosphite may be butyl hypophosphite, methyl ethyl hypophosphite, including but not limited to these.
[0063] The phosphoric acid polyester is dimethyl methylphosphonate, tributyl phosphate, etc., including but not limited to them.
[0064] The phosphite polyol may be dipropyl phosphite, dibutyl phosphite, tributyl phosphite, trimethyl phosphite, including but not limited to these.
[0065] In the present application, the copper powder is selected from spherical, flaky or dendritic powders with a D50 of 100nm to 10μm, preferably spherical or flaky powders with a D50 of 500nm to 2μm. For simple flaky or spherical copper powders within the selected particle size range, the smaller the particle size, the more contact sites between the copper powders, and the better the conductivity.
[0066] The particle size of the copper powder can be 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm or 10μm.
[0067] In the present application, the resin is selected from one or more of epoxy resin, polyurethane modified epoxy resin, acrylic modified epoxy resin, polyamide resin, saturated polyester resin, polyurethane resin, acrylic resin and silicone resin, preferably epoxy resin, acrylic modified epoxy resin, polyurethane resin. For example, polyurethane modified epoxy resin XP-3307, bisphenol F epoxy resin F170, hydrogenated epoxy resin HE-5080, polyurethane resin 5836P, including but not limited to these.
[0068] In the present application, the curing agent is selected from one or more of polyamine, anhydride, polyamide, polyol and blocked isocyanate, preferably polyamine, anhydride and blocked isocyanate. The curing agent can be, for example, 4.4'-diaminodiphenylmethane, hexahydrophthalic anhydride, methyl nadic anhydride, blocked isocyanate BI 7981, including but not limited to these, as long as it can achieve the effect in the present application.
[0069] In the present application, the accelerator is selected from one or more of tertiary amines, quaternary ammonium salts, imidazoles, pyridines, organotin and boron trifluoride complexes. For example, the accelerator can be triethanolamine, diethylbenzylamine, tetrabutylammonium bromide, 2-ethyl-4-methylimidazole, 3,5-dimethylpyrazole, 2-chloropyridine, dibutyltin dilaurate, boron trifluoride ethylamine complex, including but not limited to these, as long as the effect in the present application can be achieved.
[0070] In the present application, the solvent is selected from one or more of hydroxyl-containing compounds having a carbon number of 2 to 16, ether-containing compounds having a carbon number of 2 to 18, carbonyl-containing compounds having a carbon number of 3 to 12, and ester-containing compounds having a carbon number of 2 to 16. For example, the solvent may be terpineol, isophorone diamine, xylene, butyl acetate, diethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol butyl ether, diethylene glycol methyl ether acetate, diethylene glycol butyl ether acetate, diol esters, including but not limited to these, as long as the effects in the present application can be achieved.
[0071] In the present application, the auxiliary agent is selected from one or more of a dispersant, a coupling agent, an anti-settling agent and an acid-base regulator.
[0072] Specifically, the role of the dispersant is to promote the uniform dispersion of solid particles such as copper powder in organic media such as resin to form a stable suspension system, the role of the coupling agent is to improve the adhesion between the conductive copper slurry and the substrate, the role of the anti-settling agent is to form an electrostatic repulsion between the powders, thereby slowing down the precipitation of the powders in the slurry. The role of the acid-base regulator is to adjust the pH value of the slurry to avoid the pH value of the slurry being too large or too small to affect its curing performance. The specific types of dispersants, coupling agents, anti-settling agents and acid-base regulators are not particularly limited and are all conventional materials in the art. For example, the dispersant can be HLD-6, BYK-W966, the coupling agent can be KH550, KH560, KH570, the dust suppressant can be polyglycol ether, acetyl ricinoleic acid methyl ester, and the acid-base regulator can be triethylamine, citric acid.
[0073] In the present application, the conductive reinforcing filler is selected from one or more of silver powder, aluminum powder, nickel powder, tin powder, indium powder, carbon black, graphene and carbon nanotubes.
[0074] In the present application, the viscosity of the conductive copper paste is 120-280 Pa·s (25°C), preferably 150-240 Pa·s (25°C). During screen printing, if the viscosity is too high, the pattern is prone to problems such as missing printing and virtual printing; if the viscosity is too low, the pattern is easy to diffuse and the linear shape is poor. Therefore, as long as the viscosity is within the range of 120-280 Pa·s (25°C), the screen printing pattern can be clear and continuous.
[0075] The present application also provides a method for preparing a conductive copper paste, comprising the following steps:
[0076] Step 1: Remove oxides and organic impurities on the surface of copper powder;
[0077] Specifically, an acid ethanol solution is used to clean oxides and organic impurities on the surface of the copper powder.
[0078] The mass volume ratio of the copper powder to the ethanol solution of the acid is 1:(1-2);
[0079] In the acid ethanol solution, the mass fraction of the acid is 1-5%.
[0080] The acid is one of dilute hydrochloric acid, formic acid, oleic acid or phosphoric acid.
[0081] Step 2: Prepare the resin carrier: add the resin and antioxidant into the solvent, heat at 25-80°C for 5-120 minutes to dissolve and obtain the resin carrier.
[0082] Step 3: slurry mixing: the copper powder without oxides and organic impurities, conductive reinforcing filler, curing agent, accelerator, auxiliary agent and resin carrier are mixed and dispersed uniformly to obtain the conductive copper slurry;
[0083] The antioxidant is a compound containing phosphorus.
[0084] In the present application, the method for preparing an electrode using the conductive copper slurry is as follows:
[0085] The conductive copper paste is screen-printed onto a substrate and cured at 160-200° C. for 15-45 minutes in a nitrogen atmosphere to form an electrode. It should be noted that the specific material of the substrate is not particularly limited, and those skilled in the art can select it at will according to actual needs. As a preferred solution, the substrate is a silicon substrate.
[0086] The present application also proposes a solar cell. The solar cell has the aforementioned electrode containing a conductive copper paste. As a result, the solar cell has a more excellent conductivity, further meeting the needs of consumers. It should be noted that the antioxidant conductive copper paste is suitable for all types of solar cells, especially for HIT solar cells (crystalline silicon heterojunction solar cells). Because the conductive copper paste described in the present application is a low-temperature curing copper paste with a curing temperature below 200°C, the TCO layer of the HIT solar cell does not require special treatment, and only needs to be screen printed and heated to cure the copper paste to achieve good conductivity.
[0087] Example
[0088] The implementation methods used in the following embodiments are all conventional methods unless otherwise specified.
[0089] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0090] Example 1
[0091] The preparation method of the conductive copper paste of this embodiment is as follows:
[0092] Removal of oxides and organic impurities on the surface of copper powder:
[0093] Take 80g of flaky copper powder with a particle size D50 of 800nm and 20g of spherical copper powder with a particle size D50 of 300nm, add them into a 250mL beaker, add 100mL of 5% by mass formic acid ethanol solution, wash for 30min under stirring, centrifuge, pour out the supernatant, wash the copper powder three times with 50mL of anhydrous ethanol, centrifuge, pour out the supernatant, and bake the copper powder at 45°C in an oven with a vacuum degree of <-0.095MPa for 4h to obtain copper powder with oxides and organic impurities removed.
[0094] Preparation of resin support:
[0095] 55 g of polyurethane modified epoxy resin XP-3307 was mixed with 37 g of pine alcohol and 8 g of octadecyl phosphate monoester, and dispersed and stirred for 10 min with a high-speed stirrer at room temperature to obtain a diluted resin carrier.
[0096] Mixing:
[0097] Copper powder from which oxides and organic impurities were removed, resin carrier, curing agent blocked isocyanate BI7960, accelerator 2-ethyl-4-methylimidazole, coupling agent KH 560, and graphite powder with a particle size D50 of 1 μm were mixed in a mass ratio of 86:9.6:3.1:0.3:0.5:0.5, dispersed and mixed using a three-roll mill, and then dispersed twice using a vacuum planetary deaerator and the air in the slurry was removed to obtain a conductive copper slurry with a viscosity of 180-230 Pa·s (25°C). The parameters are shown in Table 1.
[0098] The conductive copper paste was cured in a nitrogen atmosphere oven, and then the film thickness and square resistance of the cured film were tested. The test results are shown in Table 2, where A and B represent parallel experiments. The conductive copper paste cured sample was placed at room temperature (environment temperature 25±2°C, humidity 45±5%) for 6 months, and then its square resistance was measured. The test results are shown in Table 2. The conductive copper paste cured sample was oxidized at 180°C for 60 minutes in a general blast oven, and then its square resistance was measured. The test results are shown in Table 2.
[0099] Example 2
[0100] Removal of oxides and organic impurities on the surface of copper powder:
[0101] Take 50g of flaky copper powder with a particle size of D50=3μm and 50g of spherical copper powder with a particle size of D50=1μm and put them into a 250mL beaker, add 100mL of 3% hydrochloric acid ethanol solution by mass, wash for 15min under stirring, centrifuge, pour out the supernatant, wash the copper powder three times with 50mL of anhydrous ethanol, centrifuge, pour out the supernatant, and bake the copper powder at 35°C in an oven with a vacuum degree of <-0.095MPa for 5h to obtain copper powder with oxides and organic impurities removed.
[0102] Preparation of resin support:
[0103] 53 g of bisphenol F epoxy resin F170, 11 g of 1,6-hexanediol diacrylate resin, 17 g of isophorone, 11 g of terpineol, and 8 g of n-dodecyl phosphate were mixed, and dispersed and stirred for 15 minutes using a high-speed stirrer at room temperature to obtain a diluted resin carrier.
[0104] Mixing:
[0105] The pickled copper powder, resin carrier, curing agent blocked isocyanate BI7950, accelerator boron trifluoride benzylamine complex, dispersant AKN-2111, and indium powder with a particle size of D50 = 500 nm were mixed in a mass ratio of 88:7.2:3.6:0.4:0.3:0.5, dispersed and mixed with a three-roll grinder, and then dispersed twice with a vacuum planetary degassing machine and the air in the slurry was removed to obtain a conductive copper slurry with a viscosity of 150-190 Pa·s (25°C). Its parameters are shown in Table 1.
[0106] The conductive copper paste was cured in a nitrogen atmosphere oven, and then the film thickness and square resistance of the cured film were tested. The test results are shown in Table 2, where A and B represent parallel experiments. The conductive copper paste cured sample was placed at room temperature (environment temperature 25±2°C, humidity 45±5%) for 6 months, and then its square resistance was measured. The test results are shown in Table 2. The conductive copper paste cured sample was oxidized at 180°C for 60 minutes in a general blast oven, and then its square resistance was measured. The test results are shown in Table 2.
[0107] Example 3
[0108] Removal of oxides and organic impurities on the surface of copper powder:
[0109] Take 95g of flaky copper powder with a particle size of D50 = 1μm and 5g of dendritic copper powder with a particle size of D50 = 5μm and add them to a 250mL beaker, add 100mL of 2.5% by mass ethanol phosphoric acid solution, wash for 20min under stirring, centrifuge, pour out the supernatant, wash the copper powder three times with 50mL of anhydrous ethanol, centrifuge, pour out the supernatant, and bake the copper powder at 50°C in an oven with a vacuum degree of <-0.095MPa for 2h to obtain copper powder with oxides and organic impurities removed from the surface.
[0110] Preparation of resin support:
[0111] 41 g of hydrogenated epoxy resin HE-5080, 51 g of diethylene glycol butyl ether acetate, and 8 g of di-n-butyl phosphite were mixed, heated to 40° C., and dispersed and stirred for 10 minutes using a high-speed stirrer to obtain a diluted resin carrier.
[0112] Mixing:
[0113] The pickled copper powder, resin carrier, curing agent 4,4'-diaminodiphenyl sulfone, accelerator triethanolamine, dispersant ED2020, and silver powder with a particle size of D50 = 200 nm were mixed in a mass ratio of 85:8.3:4.4:0.5:0.5:1.3, dispersed and mixed with a three-roll grinder, and then dispersed twice with a vacuum planetary deaerator and the air in the slurry was removed to obtain a conductive copper slurry with a viscosity of 160-210 Pa·s (25°C). Its parameters are shown in Table 1.
[0114] The conductive copper paste was cured in a nitrogen atmosphere oven, and then the film thickness and square resistance of the cured film were tested. The test results are shown in Table 2, where A and B represent parallel experiments. The conductive copper paste cured sample was placed at room temperature (environment temperature 25±2°C, humidity 45±5%) for 6 months, and then its square resistance was measured. The test results are shown in Table 2. The conductive copper paste cured sample was oxidized at 180°C for 60 minutes in a general blast oven, and then its square resistance was measured. The test results are shown in Table 2.
[0115] Example 4
[0116] Removal of oxides and organic impurities on the surface of copper powder:
[0117] Take 100g of flaky copper powder with a particle size of D50 = 2μm and add it to a 250mL beaker, add 100mL of 2.5% by mass ethanol phosphoric acid solution, wash for 20min under stirring, centrifuge, pour out the supernatant, wash the copper powder three times with 50mL of anhydrous ethanol, centrifuge, pour out the supernatant, and bake the copper powder at 50°C in an oven with a vacuum degree of <-0.095MPa for 2h to obtain copper powder with oxides and organic impurities removed from the surface.
[0118] Preparation of resin support:
[0119] 46 g of polyurethane resin 5836P, 9 g of epoxy acrylic resin JZ101Q, 31 g of propylene glycol butyl ether, 5 g of pineol, and 9 g of ethanolamine phosphate were mixed and dispersed evenly with a high-speed stirrer to obtain a diluted resin carrier.
[0120] Mixing:
[0121] The pickled copper powder, resin carrier, curing agent blocked isocyanate BI7982, accelerator 2-heptadecylimidazole, dispersant polyamide wax, and aluminum powder with a particle size of D50 = 500 nm were mixed in a mass ratio of 88:6.4:3.2:0.4:0.6:1.4, dispersed and mixed with a three-roll grinder, and then dispersed twice with a vacuum planetary degassing machine and the air in the slurry was removed to obtain a conductive copper slurry with a viscosity of 130-180 Pa·s (25°C). Its parameters are shown in Table 1.
[0122] The conductive copper paste was cured in a nitrogen atmosphere oven, and then the film thickness and square resistance of the cured film were tested. The test results are shown in Table 2, where A and B represent parallel experiments. The conductive copper paste cured sample was placed at room temperature (environment temperature 25±2°C, humidity 45±5%) for 6 months, and then its square resistance was measured. The test results are shown in Table 2. The conductive copper paste cured sample was oxidized at 180°C for 60 minutes in a general blast oven, and then its square resistance was measured. The test results are shown in Table 2.
[0123] The differences between Examples 5-10 and Examples 27-28 and Example 2 are that the contents of copper powder, resin, curing agent, accelerator, antioxidant, solvent, auxiliary agent, and conductive reinforcing filler are different. Details are shown in Tables 1 and 2.
[0124] The difference between Example 11 to Example 16 and Example 2 is that the types of antioxidants are different, and details are shown in Table 1 and Table 2.
[0125] The difference between Example 17 and Example 2 is that the types of resins are different, and details are shown in Table 1 and Table 2.
[0126] The difference between Example 18 and Example 19 and Example 17 is that the content of resin is different. For details, see Table 1 and Table 2.
[0127] The difference between Example 20 and Example 21 and Example 17 is that the content of antioxidant is different, and details are shown in Table 1 and Table 2.
[0128] The difference between Example 22 and Example 17 is the type of solvent, see Table 1 and Table 2 for details.
[0129] The difference between Example 23 and Example 22 is the different content of the solvent, see Table 1 and Table 2 for details.
[0130] The difference between Example 24 to Example 26 and Example 2 is that the content of the curing agent is different, and details are shown in Table 1 and Table 2.
[0131] Comparative Example 1 is Example 1 of Chinese patent application with application number 202111130893.8, and its parameters are shown in Tables 1 and 2.
[0132] Comparative Example 2 is Example 4 of the Chinese patent application with application number 202111130893.8, and its parameters are shown in Tables 1 and 2.
[0133] Table 1 shows the performance parameters of various embodiments and comparative examples.
[0134]
[0135]
[0136]
[0137] Table 2 shows the performance parameters of each embodiment and comparative example.
[0138]
[0139]
[0140] Summary: It can be seen from the above table that the conductive copper paste prepared in the embodiment of the present application has a sheet resistance as low as 2.64mΩ / square, and the sheet resistance is still very low after 6 months at room temperature and after oxidation at 180°C for 60 minutes, wherein the sheet resistance can be as low as 2.71mΩ / square after 6 months at room temperature, and as low as 5.35mΩ / square after oxidation at 180°C for 60 minutes, and the curing temperature of the conductive copper paste is low and the curing time is short. However, the conductive copper paste prepared in comparative examples 1-2 has a high sheet resistance due to the mismatch of the components, resulting in excessive or low viscosity of the conductive copper paste, poor screen printing graphics, and at the same time, since the antioxidant is not the optimal formula, its sheet resistance increases rapidly at room temperature, and the sheet resistance rises sharply at high temperature. Therefore, the conductive copper paste described in the present application has good electrical conductivity, antioxidant stability and high-temperature antioxidant effect, and can be used as an electrode material in the fields of solar cells.
[0141] Although the embodiments of the present application are described above, the present application is not limited to the above specific embodiments and application fields, and the above specific embodiments are merely illustrative and instructive, rather than restrictive. A person of ordinary skill in the art can make many forms under the guidance of this specification and without departing from the scope of protection of the claims of the present application, all of which belong to the protection of the present application.
Claims
1. A conductive copper paste, It is characterized in that Including copper powder, resin and antioxidant; The antioxidant is a compound containing phosphorus; The compound containing phosphorus element is monobasic phosphate, and the monobasic phosphate is a C4-C18 straight-chain alkyl phosphate monoester.
2. The conductive copper paste according to claim 1, It is characterized in that The conductive copper paste also includes a curing agent, a accelerator, a solvent, an auxiliary agent and a conductive reinforcing filler.
3. The conductive copper paste according to claim 1 or 2, It is characterized in that Based on the total weight of the conductive copper paste as 100%, the mass fraction of the copper powder is 78-90%, or the mass fraction of the antioxidant is 0.5-1.5%.
4. The conductive copper paste according to claim 3, It is characterized in that The mass fraction of the copper powder is 83-88%.
5. The conductive copper paste according to claim 3, It is characterized in that The mass fraction of the antioxidant is 0.5-1.2%.
6. The conductive copper paste according to claim 2, It is characterized in that Based on the total weight of the conductive copper paste as 100%, the mass fraction of the resin is 3-6.5%, or The mass fraction of the curing agent is 3-5.5%, or The mass fraction of the accelerator is 0.2-1%, or The mass fraction of the solvent is 1-5%, or The mass fraction of the auxiliary agent is 0.3-0.7%, or The mass fraction of the conductive reinforcing filler is 0.5-2%.
7. The conductive copper paste according to claim 6, It is characterized in that Based on the total weight of the conductive copper paste being 100%, the mass fraction of the resin is 3-5.5%.
8. The conductive copper paste according to claim 6, It is characterized in that The mass fraction of the curing agent is 3-5%.
9. The conductive copper paste according to claim 6, It is characterized in that The mass fraction of the accelerator is 0.2-0.6%.
10. The conductive copper paste according to claim 6, It is characterized in that The mass fraction of the solvent is 2-5%.
11. The conductive copper paste according to claim 6, It is characterized in that The mass fraction of the auxiliary agent is 0.3-0.6%.
12. The conductive copper paste according to claim 6, It is characterized in that The mass fraction of the conductive reinforcing filler is 0.5-1.5%.
13. The conductive copper paste according to claim 1, It is characterized in that The copper powder is selected from spherical, flaky or dendritic powders with a D50 of 100 nm to 10 μm.
14. The conductive copper paste according to claim 1, It is characterized in that The resin is selected from one or more of epoxy resin, polyurethane-modified epoxy resin, acrylic-modified epoxy resin, polyamide resin, saturated polyester resin, polyurethane resin, acrylic resin and silicone resin.
15. The conductive copper paste according to claim 2, It is characterized in that The curing agent is selected from one or more of polyamine, acid anhydride, polyamide, polyol and blocked isocyanate.
16. The conductive copper paste according to claim 2, It is characterized in that The accelerator is selected from one or more of tertiary amines, quaternary ammonium salts, imidazoles, pyridines, organic tins and boron trifluoride complexes.
17. The conductive copper paste according to claim 2, It is characterized in that The solvent is selected from one or more of hydroxyl-containing compounds having 2 to 16 carbon atoms, ether-containing compounds having 2 to 18 carbon atoms, carbonyl-containing compounds having 3 to 12 carbon atoms, and ester-containing compounds having 2 to 16 carbon atoms.
18. The conductive copper paste according to claim 2, It is characterized in that The auxiliary agent is selected from one or more of a dispersant, a coupling agent, an anti-settling agent and an acid-base regulator.
19. The conductive copper paste according to claim 2, It is characterized in that The conductive reinforcing filler is selected from one or more of silver powder, aluminum powder, nickel powder, tin powder, indium powder, carbon black, graphene and carbon nanotubes.
20. A method for preparing a conductive copper paste, It is characterized in that The steps include: Remove oxides and organic impurities from the surface of copper powder; Preparation of resin carrier: adding resin and antioxidant into solvent, heating and dissolving to obtain resin carrier; Slurry mixing: mixing and uniformly dispersing the copper powder from which oxides and organic impurities have been removed, conductive reinforcing filler, curing agent, accelerator, auxiliary agent and resin carrier to obtain the conductive copper slurry; The antioxidant is a compound containing phosphorus; The compound containing phosphorus element is monobasic phosphate, and the monobasic phosphate is a C4-C18 straight-chain alkyl phosphate monoester.
21. The method according to claim 20, It is characterized in that An acidic ethanol solution is used to clean oxides and organic impurities on the surface of the copper powder.
22. The method according to claim 21, It is characterized in that The mass volume ratio of the copper powder to the ethanol solution of the acid is 1 g: (1-2) ml; In the ethanol solution of the acid, the mass fraction of the acid is 1-5%; The acid is one of dilute hydrochloric acid, formic acid, oleic acid or phosphoric acid.
23. The method according to any one of claims 20 to 22, It is characterized in that The conductive copper paste prepared by the method is the conductive copper paste according to any one of claims 1 to 19.
24. An electrode, It is characterized in that The conductive copper paste according to any one of claims 1 to 19 is coated on a substrate by screen printing to form an electrode.
